2011
DOI: 10.1002/jcla.20442
|View full text |Cite
|
Sign up to set email alerts
|

Increased level of serum Homocysteine in vitiligo

Abstract: An increased serum Hcy may be a precipitating factor for vitiligo in the predisposed individuals. Serum Hcy is related to the gender of patients, activity of disease, and dietary habits of vitiligo patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 11 publications
2
33
2
1
Order By: Relevance
“…This finding coincided with the findings of Singh S et al 20 There was no statistically significant association between the duration of disease and Vitamin D3 deficiency (p value 0.532). [Table 4] Measurement of serum levels of vitamin D3 and B12 at the time of diagnosis of vitiligo is recommended and their supplementation is suggested to those suffering from the deficiencies of the same.…”
Section: Resultssupporting
confidence: 92%
“…This finding coincided with the findings of Singh S et al 20 There was no statistically significant association between the duration of disease and Vitamin D3 deficiency (p value 0.532). [Table 4] Measurement of serum levels of vitamin D3 and B12 at the time of diagnosis of vitiligo is recommended and their supplementation is suggested to those suffering from the deficiencies of the same.…”
Section: Resultssupporting
confidence: 92%
“…In clinical studies, recent evidence demonstrated that the level of total Hcy (tHcy) was significantly elevated in patients with vitiligo, and was more obvious in those patients in the active stage of vitiligo. 2,[17][18][19] The abnormal Hcy level was found to be significantly associated with distribution and bilaterality of lesions in vitiligo. [17][18][19] Additionally, depigmentation of the skin and hair was observed in patients with homocystinuria, which was described as 'pigmentary dilution'.…”
mentioning
confidence: 92%
“…It has been reported that Hcy with abnormal metabolism and quantity or function is associated with many diseases, including vitiligo. In clinical studies, recent evidence demonstrated that the level of total Hcy (tHcy) was significantly elevated in patients with vitiligo, and was more obvious in those patients in the active stage of vitiligo . The abnormal Hcy level was found to be significantly associated with distribution and bilaterality of lesions in vitiligo .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Singh et al .,[23] studied homocysteine (Hcy) levels in serum of active and stable vitiligo patients and controls. They found that there was a significant relationship between Hcy level and activity of vitiligo.…”
Section: Biochemical Parametersmentioning
confidence: 99%